Disentangling grazing and light controls on algal communities in grassland and afforested streams - Cibils Martina, Luciana (2019)
Our aim was to analyze the combined effect of grazing and light on composition, structure, functional diversity (FD) and succession of algal communities in two headwater streams (grassland and pine afforested). We hypothesized that algal communities in the grassland stream are top-down controlled, as a result of higher grazing; meanwhile, in the afforested stream, algal communities are bottom-up shaped, mainly due to sunlight reduction. In in situ experiments, we used platforms to avoid grazing in both streams, and the substrates were extracted at 23, 45 and 73 days. Algal community composition was different between stream types. Seventy percent of structural and biomass variables responded to grazing. In the grassland stream, grazing reduced richness and ash-free dry mass (AFDM), especially after 45 days, while in the afforested stream, at the same time, grazed substrates showed higher richness and AFDM than ungrazed substrates. Net grazing effect was higher on algal biomass of grassland streams. Then, 30% of functional traits showed grazing effect. High profile algae predominated in the grassland stream, where ungrazed substrates showed higher proportions of species with pad mucilage and colonial life form. Algal communities in the afforested stream remained at an early stage of succession, with a predominance of small and low profile algae in both substrates, and FD and evenness indices were lower. Our results indicate that the relative strength of top-down versus bottom-up control is different among stream types and the primary regulatory factor of freshwater communities can be modified according to such forestry practice.